Factors affecting activity of catechol 2, 3-dioxygenase from 2-chlorophenol-degrading Stenotrophomonas maltophilia strain KB2. (June 2013) - Wojcieszyńska, Danuta; Hupert-Kocurek, Katarzyna; Guzik, Urszula
Abstract The effect of phenol on 2-chloro- and 2, 4-dichlorophenol degradation by Stenotrophomonas maltophilia KB2 has been studied. During this study, we observed induction of catechol 2, 3-dioxygenase (C23O). Since, in the environment, compounds which inhibit C23O activity are frequently present together with the main dioxygenase substrates, the main aim of this work was to determine the influence of various inhibitors and activators on the enzyme activity. Hydrogen peroxide of 60 μM concentration caused total inhibition of the enzyme. Addition of ascorbic acid suppressed the inhibitory effect of hydrogen peroxide. In its presence, 60 μM hydrogen peroxide caused only 40% inhibition of C23O activity. A positive effect in preventing C23O activity was observed also in the presence of chelators (8-hydroxyquinoline, EDTA, and phenanthroline). Most metal ions and aliphatic and aromatic hydroxylated derivatives caused a 20–40% decrease in enzyme activity. The results obtained indicate that C23O from Stenotrophomonas maltophilia strain KB2 holds great potential for bioremediation.